Effectiveness of Flipbook-Based E-Jobsheets on Students’ Practical Competence in Zigzag Hair Perming Design - Wisri Ardhita Manda Putri; Habibah Hanim Lubis; Fitri Amaliyah Batubara Batubara; Irmiah Nurul Rangkuti; Mei Alsih Sihombing; Putri Chairina Zulfiani (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
The integration of digital learning media in vocational education is essential to enhance students’ practical competence, particularly in cosmetology. This study examines the effectiveness of flipbook-based e-jobsheets in improving students’ competence in zigzag hair perming design. A quantitative quasi-experimental design with a pretest–posttest control group was applied to 56 undergraduate students, divided into an experimental group (n = 28) and a control group (n = 28). The experimental group used flipbook-based e-jobsheets, while the control group used conventional job sheets. Data was collected through performance-based assessments and analyzed using descriptive statistics, normalized gain, and independent samples t-test. The results show that the experimental group achieved significantly higher posttest scores than the control group, with a high normalized gain (g = 0.72) compared to a moderate gain in the control group (g = 0.33). The difference was statistically significant (p < 0.05) with a large effect size (d = 1.83). These findings indicate that flipbook-based e-jobsheets effectively enhance students’ practical competence and support more engaging, student-centered vocational learning.